Archive of Jewish History : Volume 12. - Budnitskii, Oleg. (Boston, MA : Academic Studies Press, 2022)
The published materials are based on documents extracted from various archives in Moscow, Kyiv, New York, Jerusalem and Leeds.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books